2021
DOI: 10.1021/acsaem.1c00108
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency and Stable Organic Solar Cells with Stacked LiF and Organic Electrolytes as Cathode Interface Layers

Abstract: The cathode interfacial layer plays a key role in enhancing the efficiency and stability of organic solar cells. Constructing efficient two-layer interfaces is one of the important strategies to improve device performance. In this work, we deposited a thin layer of lithium fluoride (LiF) beneath the electron transport layer poly[(9,9bis(3′-((N,N-dimethyl)-N-ethylammonium)-propyl)-2,7-fluorene)-alt-2,7-(9,9dioctylfluorene)]dibromide (PFN-Br) and (N,N-dimethyl-ammonium N-oxide)propyl perylene diimide (PDINO), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Evidently, the cells with 2N-SAM outperform those with bare ZnO in terms of their J SC , while their V OC and FF remain constant and are equivalent to those of conventional devices (ITO/PEDOT:PSS/PM6:Y6/L-PFN-Br/Ag). 41 We demonstrated that the higher J SC is due to the hydrogen bonds between Y6 and 2N-SAM, the better WF alignment between ZnO and Y6, and the better stratification in BHJ.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Evidently, the cells with 2N-SAM outperform those with bare ZnO in terms of their J SC , while their V OC and FF remain constant and are equivalent to those of conventional devices (ITO/PEDOT:PSS/PM6:Y6/L-PFN-Br/Ag). 41 We demonstrated that the higher J SC is due to the hydrogen bonds between Y6 and 2N-SAM, the better WF alignment between ZnO and Y6, and the better stratification in BHJ.…”
Section: Resultsmentioning
confidence: 72%
“…Evidently, the cells with 2N-SAM outperform those with bare ZnO in terms of their J SC , while their V OC and FF remain constant and are equivalent to those of conventional devices (ITO/PEDOT:PSS/PM6:Y6/L-PFN-Br/Ag). 41 We demonstrated Fig. 2 The FT-IR spectra of Y6, 2N-SAM and the 2N-SAM/Y6 (w/w, 1 : 1) blend.…”
Section: Vertical Phase Separationmentioning
confidence: 97%
“…This knowledge can then be used to tailor and optimize materials to create more efficient and stable organic electronic devices. [123] Copyright 2021, American Chemical Society.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, PTB7:PC 71 BM based OSCs with TiO x /PEI gave a much increased PCE of 9.08%, compared to the 7.00% and 7.38% for those with individual PEI or TiO x as the ETL, respectively. Jiang and Fang et al employed a fullerene derivative C60 pyrrolidine tris-acid 113 The LiF layer was deposited by vacuum evaporation with ca. 1 nm thickness, which can act as the optical spacer layer to optimize the light intensity distribution resulting in better light harvesting.…”
Section: Hybrid Double Layer Cilsmentioning
confidence: 99%
“…Recently, Yang and Zhao et al reported a kind of double layer CIL of LiF/PFNBr or LiF/PDINO in conventional OSCs. 113 The LiF layer was deposited by vacuum evaporation with ca. 1 nm thickness, which can act as the optical spacer layer to optimize the light intensity distribution resulting in better light harvesting.…”
Section: Metal Oxide-based Hybrid Cilsmentioning
confidence: 99%